Development of Optical Sensor Technology for Non-Invasive Hemoglobin Measurement - Muthmainnah; Fabriansyah Zakaria Arabani; Imam Tazi; Ninik Chamidah; Wiwis Sasmitaninghidayah; Mokhamad Tirono (Postgraduate, University of Mataram, 2023)
This research focuses on the development of hardware and software required to implement optical sensor technology. The optical sensor used is the MAX30102, equipped with infrared (IR) and red-light sources along with a receiver. The signals generated by the sensor are processed by NodeMCU and displayed on the OLED. The calibration results indicate the relationship between hemoglobin obtained using the invasive method and the output of the MAX30102 sensor, which is in the form of wavelength. It has the equation Â with an Â value of 0.9114. This equation is utilized to program the NodeMCU through the Arduino IDE. Validation and clinical trials have been conducted to evaluate its accuracy and applicability in clinical contexts. The results show that the non-invasive device has an average standard deviation of 0.32, indicating consistent measurement values. The non-invasive device demonstrates an average accuracy of 99.24%, signifying high precision and similarity to invasive methods. This suggests that the device holds potential as an innovative solution for Hemoglobin measurement.